A survey on students' acceptance towards online reading practice and its impact on students' reading comprehension achievement / Muhammad Aimanuddin Mohd Zaki - Mohd Zaki, Muhammad Aimanuddin (2015)
In Malaysia, many course developers revised the course design so the course can meet the demand of 21st century. The presence of technology in educational field has transformed the reading style. Online reading starts to be trend in tertiary education. The current study reveals the number of high achieving students who accept and do not accept online reading practice. The aim of the study is to determine whether the relationship between high achieving students' acceptance towards online reading with their performance in learning English existed. Previous studies established that students' acceptance towards online reading has relationship with their performance in learning English. The current study revealed the relationship between high achieving students' acceptance with their performance in learning English in this public university setting. In this study, the researcher employed Technology Acceptance Model (TAM) as the theoretical framework. The questionnaire was adopted from a study that employed the same theoretical framework. The quantitative approach was used for the data collection process. A total of 201 respondents who scored good grades (A and B) in ELC 150 course were asked to answer the questionnaires. However, the researcher found that only 141 set of questionnaires were valid for the data analysis while the remaining questionnaires were invalid. The ages of the respondents were ranged from 18 to 20 years old. After the data was analyzed, the researcher found that majority of high achieving students accepted online reading practice. The researcher also found positive relationship between high achieving students' acceptance towards online reading practice with their performance in learning English. The result indicated that high achieving students' acceptance towards online reading practice with their performance in learning English. Among all respondents, 64 of them accepted online reading practice while 10 of the respondents rejected. The data also indicates that students' interest (SI) in online reading practice has the most significant relationship with achievement in final examination where the significance value is .985.